2015
DOI: 10.1108/ijphm-10-2013-0055
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward acupuncture in Hong Kong

Abstract: We would like to thank the students in Integrated Communication Management program for data collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Overall, respondents demonstrate lack of trust in TCM. The lack of trust in TCM is built on doubts about the experience and qualifications of TCM practitioners. The central issue of trust in choosing medical treatment found in this study echoes the findings reported in previous studies of decisions about acupuncture treatment using qualitative, as well as quantitative, methodologies (Chan et al , 2015a; Chan et al , 2016). The current study indicates that trust in TCM is related to trust in the system governing TCM practices, as well as trust in TCM practitioners.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Overall, respondents demonstrate lack of trust in TCM. The lack of trust in TCM is built on doubts about the experience and qualifications of TCM practitioners. The central issue of trust in choosing medical treatment found in this study echoes the findings reported in previous studies of decisions about acupuncture treatment using qualitative, as well as quantitative, methodologies (Chan et al , 2015a; Chan et al , 2016). The current study indicates that trust in TCM is related to trust in the system governing TCM practices, as well as trust in TCM practitioners.…”
Section: Discussionsupporting
confidence: 87%
“…The questionnaire was adapted from a previous study on public attitudes toward acupuncture in Hong Kong (Chan et al, 2015a). Attitude toward biomedicine in relation to TCM as a medical treatment was measured by seven statements using a five-point scale with "1" indicating "disagree strongly" and "5" indicating "agree strongly".…”
Section: Methodsmentioning
confidence: 99%
“…In a survey conducted in Hong Kong, study participants perceived strengths of acupuncture as having fewer side effects and as being effective for preventive care. 34 According to a Malaysian study, the majority (78.5%) of study participants agreed that TM had less side effect when compared with conventional medicine. 32 …”
Section: Main Textmentioning
confidence: 99%
“…8,1214 On the contrary, patients reluctant to try acupuncture report having doubts about its efficacy and scientific basis. 6,15 Expectations of acupuncture treatment outcome affecting participants’ responses vary among studies, possibly due to the variability of measurement tools used. 16 Understanding this bias is beyond the scope of this article, and an ongoing systematic review and meta-analysis is assessing this further.…”
Section: Introductionmentioning
confidence: 99%